Employee Loyalty Analysis at PT Alove Bali IND Using a Structural Equation Modeling (SEM) Approach - Ni Kadek, Marita Dewi; Suryawardani, I Gusti Ayu Oka; Dewi, Ratna Komala (Advances in Social Sciences Research Journal, 2026)
This study aims to analyze: 1) the influence of salary, work compensation, leadership and work environment on employee satisfaction, performance and loyalty at PT Alove Bali IND, 2) the influence of satisfaction on employee performance and loyalty, 3) the influence of performance on employee loyalty, 4) the role of employee satisfaction and performance in mediating salary, compensation, leadership and work environment on employee loyalty. The study was conducted at PT Alove Bali IND in Gianyar Regency, Bali Province, which is a company that produces liquid organic fertilizer made from aloe vera, which was carried out from August to October 2025. The research location was chosen because employee loyalty is high with the majority of employees having a length of service of over five years. Data collection techniques were carried out by interviews, observations and distributing questionnaires based on the census method to all 50 employees. Data were analyzed using the Structural Equation Modeling (SEM) method and analyzed with the Smart-PLS program version 4. The results of the study showed that: 1) a) Salary does not have a significant influence on employee satisfaction, performance and loyalty, b) Work compensation has a significant influence on employee satisfaction and loyalty, c) Leadership has a significant influence on satisfaction, d) Work environment has a significant influence on employee performance and loyalty; 2) Satisfaction has a significant influence on performance; 3) Performance has a significant influence on loyalty; and 4) The results of the indirect effect test show that job satisfaction does not function as a significant mediator, both on performance and loyalty, while employee performance is a significant mediator in mediating the influence of the work environment on loyalty. It is recommended that PT Alove Bali IND maintain employee loyalty through work compensation, leadership and work environment and pay attention to employee salaries in company management so that it is expected to increase employee satisfaction.